Descriptive analysis of preschool physical activity and sedentary behaviors – a cross sectional study of 3-year-olds nested in the SKOT cohort - Niels Christian Møller (BMC Public Health, 2017)
Abstract Background Further collection of surveillance data is warranted, particularly in preschool populations, for optimizing future public health promotion strategies. This study aims to describe physical activity (PA) and sedentary behavior (SB) across different settings, including time in and out of daycare, and to determine the proportion of children complying with suggested PA recommendations in a high income country. Methods Valid PA was assessed in 231 children (36.4 ± 1.1 months) with the Actigraph GT3X accelerometer, and information regarding date and time of dropping-off/picking-up children in daycare was provided by parents. Mean total PA (i.e., counts per minute (CPM)), moderate-to-vigorous physical activity (MVPA), SB time, and non-SB time was generated and compared across settings. Post hoc, PA and SB were examined in subgroups of low-active (1st quartile) and high-active (4th quartile) children. Results Overall, boys and girls spent 1.4 ± 0.3 h/day and 1.2 ± 0.4 h/day in MVPA, respectively. Likewise, boys and girls accumulated 6.7 ± 0.8 h and 6.8 ± 0.9 h of SB time per day, respectively. Higher PA levels consistently co-occurred with lower SB time in the daycare setting. Girls accumulated less SB time in daycare than before and after daycare (β = −12.2%, p < 0.001 & β = −3.8%, p < 0.001, respectively). In boys, daycare-days contained more PA and less SB than non-daycare-days (CPM: β =29, p = 0.046, %MVPA: β = 0.83, p = 0.007, %SB: β = −2.3, p < 0.001, respectively). All children fulfilled recommendations of at least 3 h of daily non-SB. Eighty-nine percent of boys and 72% of girls met the daily 1-h MVPA recommendation for 5 year-olds. Lower proportions of children, especially boys, fulfilled MVPA recommendation on days with no daycare attendance. Generally, large mean differences in MVPA and SB were observed across all settings between the most active and the least active children, and only 7% of the low-active girls and 59% of the low-active boys fulfilled MVPA recommendations. Conclusions Overall, the majority of children fulfilled MVPA guidelines for 5 year-olds, and all children complied with suggested recommendations of 180 min of daily activity. Daycare time was found to represent an important setting for PA. Substantial and consistent differences observed in the amount of time spent physically active between high- and low-active children across all settings indicate substantial variations in young children’s PA levels irrespective of the context.